Answer:
2
Step-by-step explanation:
To be divisible by 6, an even number must also be divisible by 3. Two of every three even numbers are <em>not</em> divisible by 3, so are not divisible by 6.
Step-by-step explanation:
y=6+4x, as equation (iii)
=> -5x-(6+4x)=21
=> -5x-6-4x=21
=> -5x-4x-6=21
=> -9x-6=21
=> -9x=21+6
=> -9x=27
x= -3, by dividing both sides by -9
So, by inserting x in the first equation,
=> -4(-3)+y=6
=> 12+y=6
=> y=6-12
=> y= -6.
Therefore, x= -3 and y= -6
Answer:
the answer is c
Step-by-step explanation:hope this helped!
Answer:
im pretty sure it's P({x:x is oven-baked apple & lavender calzone })
Step-by-step explanation:
its the one with the biggest section